Respuesta :

Since p = x² - 7, you can substitute/plug in p for x² - 7

So:

(x² - 7)² - 4x² + 28 = 5

(p)² - 4x² + 28 = 5      You can factor out -4 from (-4x² + 28)

p² - 4(x² - 7) = 5        Plug in p

p² - 4p = 5        Subtract 5

p² - 4p - 5 = 0        Your answer is C

Quadratic equation is the equation in which only one unknown is present and the power of the unknown variable is 2. the equation which is equivalent to the given equation in terms of [tex]p[/tex] is,

[tex]p^2-4p=5[/tex]

Thus the option C is the correct option.

Given information-

[tex]p= x^2-7[/tex]

The given equation in the problem is,

[tex](x^2-7)^2-4x^2+28=5[/tex]

Quadratic equation

Quadratic equation is the equation in which only one unknown is present and the power of the unknown variable is 2

As it has to be convert this quadratic equation in terms of variable [tex]p[/tex]. Thus the equation has to be rewrite. Thus,

[tex](x^2-7)^2-4x^2+28=5[/tex]

[tex](x^2-7)^2-4x^2+28=5[/tex]

[tex](x^2 -7)^2-4(x^2-7)=5[/tex]

Put the value if the [tex]x^2-7[/tex] as [tex]p[/tex] in the above equation,

[tex](p)^2-4(p)=5[/tex]

[tex]p^2-4p=5[/tex]

[tex]p^2-4p-5=0[/tex]

Hence the equation which is equivalent to the given equation in terms of [tex]p[/tex] is,

[tex]p^2-4p=5[/tex]

Thus the option C is the correct option.

Learn more about the quadratic equation here;

https://brainly.com/question/17177510